Artificial Intelligence - Kaushik, Saroj (New Delhi: Centage Learning India, 2011)
This textbook Artificial Intelligence is designed to provide comprehensive material to undergraduate and graduate students on the vast and fast-growing subject of Artificial Intelligence. The book has been written keeping in mind the syllabi designed for courses on AI in various technical institutions and universities in India and abroad. The book can serve as a textbook for the first-level course for one full semester on AI and will also provide study material to computer professionals who wish to expand their knowledge. The main topics covered in the book include problem-solving using intelligent searches and planning, knowledge representation techniques, game playing, first-order predicate logic and Prolog (programming in logic) programming language, uncertainty handling, expert systems. The language Prolog has been used throughout the book to write programs for problems to be solved using AI techniques. In addition, some advanced topics such as machine learning, fuzzy logic, artificial neural network, evolutionary computing, advanced knowledge representation techniques, agent technology and natural language processing have been included in detail.
Table of ContentIntroduction to Artificial IntelligenceProblem Solving: State-Space Search and Control StrategiesProblem Reduction and Game Playing Logic Concepts and Logic Programming Prolog Programming LanguageAdvanced Problem-Solving Paradigm: Planning Knowledge Representation Expert System and Applications Uncertainty Measure: Probability Theory Fuzzy Sets and Fuzzy Logic Machine-Learning Paradigms Artificial Neural Networks Evolutionary ComputationIntroduction to Intelligent Agents Advanced Knowledge Representation Techniques Natural Language Processing References Index
Each chapter in the book has been carefully developed with the help of several pedagogical features. A large amount of effort has been put in to ensure that every concept discussed in the book is explained with the help of examples as far as possible. Pseudo algorithms for various methods and techniques are included throughout the book to increase the comprehensibility of the topics and demonstrate their applications.
Keywords: Artificial Intelligence